Open and Closed Innovation Different Cultures for Different Strategies - Herzog, Philipp; SpringerLink (Online service) (Wiesbaden : Gabler Verlag : Imprint: Gabler Verlag, 2008)
Open Innovation is a phenomenon in both research and management practice. Since radical innovation or new business development often require external technologies or ways of commercialization, many firms have shifted from a Closed to an Open Innovation model. However, firms often face difficulties during the implementation. While the implementation effort usually focuses on external ideas and technologies as well as the processes to identify them, cultural challenges are neglected. Philipp Herzog develops a theoretical framework arguing that Open Innovation and Closed Innovation cultures need to be different (e.g. regarding the not-invented-here (NIH) syndrome). Based on a multi-respondent survey among 120 R&D employees from three business units of a leading chemical firm, he provides empirical evidence for many of the hypothesized differences in innovation culture. The findings may also help firms cope with the challenges experienced in implementing the Open Innovation concept.
Innovation and the Open Innovation concept -- Innovation culture -- Conceptual framework and hypotheses -- Analysis and results -- Discussion of findings and implications for theory and practice -- Summary and conclusion.
Keywords: Management; Management